Explosion of the boundary layer upon entry of spacecraft into dense layers of the earth’s atmosphere - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: A supersonic flow around a sphere with a radius of 1m at altitudes of 80 to 40 km was analysed. Methods: The descent trajectory at the first cosmic velocity, similar to that of the Soyuz spacecraft with a duralumin structure without thermal protection, was taken into consideration. Results: For the gas between the shock wave front and the surface of the descending spacecraft, data were obtained on the increase in density, pressure, and temperature behind the shock wave front as well as the shift of the shock wave from the surface of the descending spacecraft. The effective temperature of the shock-heated gas reaches its maximum value of 7340 K at an altitude of 60 km. At altitudes of 80 and 40 km, the effective temperature is 7000 K and 6400 K, respectively. Based on the obtained data on the thermodynamic state of the gas behind the shock wave every 10 km, calculations were made of energy fluxes to the surface of the spacecraft for convective and radiative heat transfer, as well as for the impact of electrons produced due to ionization of negative ions. Radiative heat transfer has proven to be the most significant.The burning mechanism of negative ions of triatomic molecules of aluminium with the formation of AlO molecules was determined, and data on pressure rise in the boundary layer on the spacecraft surface were obtained. At all considered altitudes, the pressure rises instantly: to 1.06×1010 Pa at an altitude of 80 km, 5.3×109 Pa at an altitude of 60 km, and reaches the maximum value of 5.5×1010 Pa and an altitude of 40 km. A pressure of 109 to 1010 Pa arises during explosion of various explosives. The energy flux reaches the spacecraft surface between explosions. At the moment of explosion, shock waves develop in the atmosphere surrounding the surface of the descending spacecraft, and compressive waves develop in the entire structure of the spacecraft. The descending spacecraft cracks, and its entire structure breaks down into parts. The area of interaction increases sharply, and each subsequent explosion has a greater intensity and size. As a result, the last most intense explosion occurs at an altitude of approx. 40 km, after which individual fragments of the spacecraft fall to Earth. Conclusion: The exploration of space with flight to other planets is possible only after a thorough study of explosive processes taking place on the surface of the spacecraft descending on other planets, and especially on Earth.